DNA barcodes provide new evidence of a recent radiation in the genus Sporophila (Aves: Passeriformes) - Campagna, Leonardo (2010)
The capuchinos are a group of birds in the genus Sporophila that has apparently radiated recently, as evidenced by their lack of mitochondrial genetic diversity. We obtained cytochrome c oxidase I (COI) sequences (or DNA barcodes) for the 11 species of the group and various outgroups. We compared the patterns of COI variability of the capuchinos with those of the largest barcode data set from neotropical birds currently available (500 species representing 51% of avian richness in Argentina), and subjected COI sequences to neighbour-joining, maximum parsimony and Bayesian phylogenetic analyses as well as statistical parsimony network analysis. A clade within the capuchinos, the southern capuchinos, showed higher intraspecific and lower interspecific divergence than the remaining Argentine species. As most of the southern capuchinos shared COI haplotypes and pairwise distances within species were in many cases higher than distances between them, the phylogenetic affinities within the group remained unresolved. The observed genetic pattern is consistent with both incomplete lineage sorting and gene flow between species. The southern capuchinos constitute the only large group of species among the neotropical birds barcoded so far that are inseparable when using DNA barcodes, and one of few multispecies avian groups known to lack reciprocal monophyly. Extending the analysis to rapidly evolving nuclear and mitochondrial markers will be crucial to understanding this radiation. Apart from giving insights into the evolution of the capuchinos, this study shows how DNA barcoding can rapidly flag species or groups of species worthy of deeper study.